Internalizing religious tolerance in elementary schools: Reality and alternative solution - Rahmadonna, Sisca; Setyosari, Punaji; Kuswandi, Dedi; Praherdhiono, Hendy; Wibawa, Aji Prasetya (International Journal of Education and Learning, 2024)
Religious intolerance is rising globally, including in Indonesia, a pluralistic nation with over 600 ethnic groups and six official religions. Ironically, cases of intolerance have emerged even in Yogyakarta, an educational and cultural barometer renowned for its local wisdom of tepa selira (mutual respect). This study investigates how elementary school teachers in Yogyakarta, Indonesia understand and internalize religious tolerance in classroom practices. Employing a qualitative phenomenological approach, data were collected through interviews, observations, FGDs, and document analysis involving 20 teachers from 10 diverse elementary schools. Findings indicate that most teachers focus on cognitive outcomes and struggle to assess tolerance in the affective domain. However, one multicultural school Pelangi Elementary demonstrates an alternative approach by emphasizing shared human values such as kindness, gratitude, and togetherness, and by removing formal religious instruction to foster inclusivity. The school integrates dialogical pedagogy, parental involvement, and community engagement, making tolerance a lived experience rather than a theoretical concept. This study concludes that religious tolerance education in diverse societies must move beyond textbooks toward character-based, participatory learning rooted in local wisdom and inclusive practice. The Pelangi model offers a promising strategy adaptable to other pluralistic contexts.